2005
DOI: 10.1128/jb.187.13.4598-4606.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence that GTP Is Required for Transposition of IS 903 and Tn 552 in Escherichia coli

Abstract: Surprisingly little is known about the role of host factors in regulating transposition, despite the potentially deleterious rearrangements caused by the movement of transposons. An extensive mutant screen was therefore conducted to identify Escherichia coli host factors that regulate transposition. An E. coli mutant library was screened using a papillation assay that allows detection of IS903 transposition events by the formation of blue papillae on a colony. Several host mutants were identified that exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
(52 reference statements)
2
7
0
Order By: Relevance
“…These, and previous, studies have also indicated that transposition of IS903 occurs at late times during colony growth (Fig. 2, and Coros et al, 2005).…”
Section: Transposition and Intermediary Metabolismsupporting
confidence: 83%
See 1 more Smart Citation
“…These, and previous, studies have also indicated that transposition of IS903 occurs at late times during colony growth (Fig. 2, and Coros et al, 2005).…”
Section: Transposition and Intermediary Metabolismsupporting
confidence: 83%
“…Mutations received, or created by λRed mutagenesis were transduced into DH10B or HT321. For transduction of mutations into the recA – strain, DH10B, the recA gene was supplied in trans from a plasmid, pET001 (Coros et al ., 2005). Replication of this plasmid is temperature‐sensitive.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, stress situations such as carbon starvation, extreme temperature, and UV light have been correlated with the enhanced transposition of bacterial mobile elements (10,15,22,31,33,39). These findings support the idea that bacteria derepress the movement of mobile elements as an adaptive response to stress and to permit new traits to evolve (6,46).…”
Section: Discussionsupporting
confidence: 72%
“…This is an aspect of bacterial transposition that has not been thoroughly studied even though there are many (mostly anecdotal) examples of transposition systems responding to stress conditions. One exception is the IS903 system, in which the response of this element to defects in purine metabolism has been worked out reasonably well (28). Outside of host regulation there has been some new activity directed at further defining molecular details of the Tn5 and Tn10 hairpin reactions.…”
Section: General Backgroundmentioning
confidence: 99%